2004
DOI: 10.1002/jnr.20211
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of degeneration and new growth of axons and synaptic endings in the chinchilla cochlear nucleus after acoustic overstimulation

Abstract: To determine if acoustic overstimulation altered synaptic connections in the cochlear nucleus, anesthetized adult chinchillas, with one ear protected by a silicone plug, were exposed for 3 hr to a 108-dB octave-band noise, centered at 4 kHz, and allowed to survive for periods up to 32 weeks. This exposure led to cochlear damage in the unprotected ear, mainly in the basal regions of the organ of Corti. The anterior part of the ipsilateral posteroventral cochlear nucleus consistently contained a band of degenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
9

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 36 publications
(81 reference statements)
5
65
0
9
Order By: Relevance
“…The quantitative verification of this observation is provided in a companion study (Kim et al, 2004b). Neuronal cell bodies supplied with presumptive new synaptic endings were identified, because they were crenated, just like the heavily depopulated neuronal somata observed at earlier survival times (Kim et al, 2004a).…”
Section: New Growth Of Synaptic Endingsmentioning
confidence: 69%
See 1 more Smart Citation
“…The quantitative verification of this observation is provided in a companion study (Kim et al, 2004b). Neuronal cell bodies supplied with presumptive new synaptic endings were identified, because they were crenated, just like the heavily depopulated neuronal somata observed at earlier survival times (Kim et al, 2004a).…”
Section: New Growth Of Synaptic Endingsmentioning
confidence: 69%
“…These axons may have come from sources outside the denervated zone, and possibly outside the posteroventral cochlear nucleus itself (see Kim et al, 2004b). Regardless of the sources of the fresh endings, many of them had a novel appearance.…”
Section: Does the Synaptic Organization Of The Cochlear Nucleus Changmentioning
confidence: 99%
“…DCN neurons are relatively well tuned in unexposed animals and do not show evidence of multiple excitatory inputs from fibers with BFs that differ by an octave or more, as seems to be required for class B responses. Thus, we propose that a part of the regrowth of synaptic connections demonstrated in the DCN (Kim et al, 2004b) involves formation of new connections to DCN neurons from fibers with BFs relatively remote from the neuron's own BF; most likely this would be low-BF fibers making contact with formerly higher-BF DCN neurons. Previous studies of the tonotopic organization of the DCN following cochlear damage have not found evidence for plasticity of this type and have specifically ruled it out (Kaltenbach et al, 1992;Rajan and Irvine, 1998).…”
Section: Implications Of Class B Responsesmentioning
confidence: 99%
“…More relevant to the present work are studies in which acoustic trauma was used. Following trauma, degeneration of axons and cells in the cochlear nucleus occurs (Bilak et al, 1997;Muly et al, 2002;Kim et al, 2004b;Muly et al, 2004). The initial loss includes both excitatory and inhibitory synapses, but there is a return of excitatory synapses and of glutamate release and uptake, without a corresponding increase in inhibitory synapses.…”
Section: Mechanisms Of the Tail Responsementioning
confidence: 99%
“…Pathological changes have been found in the central auditory system, especially in the cochlear nucleus (CN), after noise exposure (Aarnisalo et al, 2000;Basta et al, 2005;Gröschel et al, 2010;Kim et al, 1997Kim et al, , 2004aMorest et al, 1998;Muly et al, 2004;Theopold, 1975). The number or density of axons in the chinchilla posterior ventral cochlear nucleus (PVCN) was decreased by about half (Bilak et al, 1997).…”
Section: Introductionmentioning
confidence: 99%